The Effect of R&D intensity, intellectual capital and managerial ability on firm’s performance with political connection as a moderating variable - Dewiruna, Intansari; Subroto, Bambang; Subekti, Imam (The Indonesian Accounting Review, 2020)
This study aims to examine and analyze the effect of Research and Development (R&D) intensity, intellectual capital, and managerial ability on firm’s performance both directly and indirectly moderated by political connection. This study uses manufacturing sector firms listed on the Indonesia Stock Exchange which were selected using a purposive sampling method, with a total of 119 data observations (2013 - 2017) and using a quantitative approach. This study uses multiple linear regression analysis and hierarchical regression analysis. The results of the study prove empirically that the firm’s performance can be improved by increasing the intensity of R&D and intellectual capital. The existence of political connections can strengthen the influence of the relationship of R&D intensity on a firm’s performance. The firm’s performance is not related to managerial ability and political connection cannot strengthen or weaken the influence of intellectual capital on managerial performance and ability.